2012
DOI: 10.6000/1927-3037/2012.01.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Everyone! The Novel Immunobiotic Lactobacillus rhamnosus CRL1505 and the Beginning of Social Probiotic Programs in Argentina

Abstract: Lactobacillus rhamnosus CRL1505 (Lr1505) stimulates immune responses in the gut and in the respiratory tract and improves resistance against Salmonella typhimurium and Streptococcus pneumoniae infections in immunocompetent and immunocompromised mice. Considering that respiratory infectious diseases continue to be a major cause of death among preschool children in developing countries, the aim of the present study was to evaluate the effect of Lr1505 on the health of children. A randomized-controlled double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
2
15
0
2
Order By: Relevance
“…In a randomized controlled trial conducted by Villena et al (44), L. rhamnosus CRL1505 (administered in a yogurt formulation) improved mucosal immunity and reduced the incidence and severity of intestinal and respiratory infection in children. Hence, the incidence of infectious events was reduced from 66% in the placebo group to 34% in the group that received the probiotic yogurt.…”
Section: Beneficial Effects Of Immunobiotics In Rotavirus Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a randomized controlled trial conducted by Villena et al (44), L. rhamnosus CRL1505 (administered in a yogurt formulation) improved mucosal immunity and reduced the incidence and severity of intestinal and respiratory infection in children. Hence, the incidence of infectious events was reduced from 66% in the placebo group to 34% in the group that received the probiotic yogurt.…”
Section: Beneficial Effects Of Immunobiotics In Rotavirus Infectionmentioning
confidence: 99%
“…Hence, the incidence of infectious events was reduced from 66% in the placebo group to 34% in the group that received the probiotic yogurt. Furthermore, there was also a significant reduction in the occurrence of indicators of disease severity such as fever and the need for antibiotic treatment in children receiving the probiotic yogurt (44). Therefore, the results of this trial suggested that consumption of yogurt containing L. rhamnosus CRL1505 was helpful to reduce the burden of common childhood morbidities, especially those associated to viral infections including RVs (44).…”
Section: Beneficial Effects Of Immunobiotics In Rotavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that this assumption was true after demonstrating increased numbers of CD3 + CD4 + IFN-γ + T in the lungs mice orally treated with L. rhamnosus CRL1505 (62). Furthermore, the mobilization of CD3 + CD4 + IFN-γ + T cells from the intestine to the airways and the higher production of IFN-γ could be involved in the improved anti-viral state induced by L. rhamnosus CRL1505 that was observed in clinical studies (5). Probably, IFN-γ secreted in response to L. rhamnosus CRL1505 stimulation would be capable of functionally modulate the innate immune microenvironment in the lung, inducing the activation of DCs (64) and macrophages (81).…”
Section: Distal Modulation Of Respiratory Anti-viral Immunity By L Rmentioning
confidence: 99%
“…More specifically, the article review the mechanisms involved in the capacity of the immunobiotic strain Lactobacillus rhamnosus CRL1505 to beneficially modulate the immune response triggered by Toll-like receptor (TLR)-3 activation in the respiratory tract and to increase the resistance to RSV infection. In addition, we will discuss the role of interferon (IFN)-γ and interleukin (IL)-10 in the immunoregulatory effect of the CRL1505 strain that has been successfully used for reducing incidence and morbidity of viral airways infections in children (5). …”
Section: Introductionmentioning
confidence: 99%